Reducing power line interference with the continuous automatic cab signalling channel - R. R. Yusupov; A. S. Khokhrin (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Interference in the continuous automatic cab signalling channel distorts transmitted signals and causes signalling malfunctions. Reduction of interference in the channel involved a previously proposed receiver with quadrature channels and its implementations with non-linear signal transformation in one or two sections of the receiver. The research is intended to find the best implementations of the quadrature receiver.Materials and methods. The research uses a computer simulation of the operation of the studied receivers under the influence of harmonic interference from a power line. For this purpose, the authors used Simulink visual programming environment and developed receiver simulations, applied the harmonic interference simulation model and conducted experiments to assess noise immunity expressed as a time interval showing receiver malfunction.Results. The researchers determined the effect of non-linear signal transformation on the harmonic noise immunity of the receivers.Discussion and conclusion. The research shows that the receiver with a deadband is the most preferable of all considered variants of quadrature receivers in terms of maximum harmonic noise immunity. The receiver with combined interference suppressor and deadband is slightly inferior.